Towards Gender-Equitable Religious Education: A Study of Thought on the Formation of Gender Equality in Islamic Education - Siti Mutmainah; Nur Khasanah (TATHO: International Journal of Islamic Thought and Sciences, 2026)
Islamic education has great potential in promoting gender equality. However, efforts to achieve this still face various challenges, such as strong patriarchal culture, structural inequality, and social resistance to change. This study aims to analyze the role of Islamic education in shaping social gender constructs and to formulate strategies for creating a more inclusive and equitable education system. Through a qualitative approach based on literature analysis, the study found that increasing understanding of gender, updating the curriculum, empowering women in educational institutions, and community involvement are important steps in creating an education system that is more responsive to gender issues. The findings show that inclusive Islamic education can reduce gender stereotypes, increase women's participation, and strengthen the value of justice in the educational process. These strategies are key to building an equitable educational environment that supports the development of the potential of all students.